2014
DOI: 10.1002/jctb.4372
|View full text |Cite
|
Sign up to set email alerts
|

N‐doped TiO2/s‐PS aerogels for photocatalytic degradation of organic dyes in wastewater under visible light irradiation

Abstract: BACKGROUND: Heterogeneous photocatalysis for the degradation of non-biodegradable organic contaminants in wastewater is an alternative to traditional treatment techniques. Since the applications developed employ photocatalysts in powder form, a main disadvantage remains related to the recovery of photocatalysts from the treated wastewater, resulting in damage and shorter lifetime for the recirculation pumps. Structured photocatalysts offer a valid solution to simplify the process; however, they have to guarant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
47
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 40 publications
(52 reference statements)
3
47
0
1
Order By: Relevance
“…To extend the TiO 2 absorption into the visible range, several laboratories have recently reported TiO 2 -F and TiO 2 -N doped PS films prepared by colloidal methods degrading organic compounds under sunlight light within a few hours J. K. Zhou et al, report degradation of MB [9], K. M. Parida et al, report degradation of methyl-orange (MO) and MB, an anionic and a cationic dye [10]. V. Viano et al, report the degradation of MB [11], L. Huang et al, [12] reports MO degradation and Z. Zheng et al, [13] et al, have reported Cu(I)O and Cu(II)O active in the photocatalytic degradation of pollutants/dyes under visible light up to 680 nm.…”
Section: Introductionmentioning
confidence: 99%
“…To extend the TiO 2 absorption into the visible range, several laboratories have recently reported TiO 2 -F and TiO 2 -N doped PS films prepared by colloidal methods degrading organic compounds under sunlight light within a few hours J. K. Zhou et al, report degradation of MB [9], K. M. Parida et al, report degradation of methyl-orange (MO) and MB, an anionic and a cationic dye [10]. V. Viano et al, report the degradation of MB [11], L. Huang et al, [12] reports MO degradation and Z. Zheng et al, [13] et al, have reported Cu(I)O and Cu(II)O active in the photocatalytic degradation of pollutants/dyes under visible light up to 680 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of oxygen and UV irradiation, organic substrates can be decomposed to CO 2 , H 2 O, or mineralized acids on the surface of photocatalysts [7,8]. Photocatalysts have often been used in two forms: suspended slurries in aqueous solutions [9,10] and immobilized powders or films on inert supports [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to support a sustainable hydrogen economy, it is crucial to produce hydrogen cleanly and renewably. Typically, heterogeneous photocatalysis is studied with the aim of removing organic pollutants from wastewater [19,20] through oxidation reactions which can finally result in the production of CO 2 and water. An interesting approach is to explore, in parallel to wastewater treatment, opportunities of mass recovery which can be sold as secondary raw material or used as energy resources, such as hydrogen and methane.…”
Section: Introductionmentioning
confidence: 99%